A pilot study on the establishment of national ambient noise monitoring network across the major cities of India. (February 2016) - Garg, N.; Sinha, A.K.; Gandhi, V.; Bhardwaj, R.M.; Akolkar, A.B.
Highlights: National Ambient Noise Monitoring Network is described. Ambient day and night sound levels across seven major cities of India is described. The study shows the difference of ( L day − L night ) since past three years across the seven major cities in India. Abstract: The paper describes the pilot project on the establishment of National Ambient Noise Monitoring Network ( NANMN ) across seven major cities in India for continuous noise monitoring throughout the year. The annual average L day (06–22 h) and L night (22–06 h) values observed since past three years are described. The long-term noise monitoring shows that ambient noise levels have marginally increased since past three years in the 35 locations under study in which 14 locations are in commercial zone, 5 in Industrial, 7 in residential and 9 in silence zones. The study is very helpful in ascertaining the magnitude of annual average ambient noise levels, planning for noise abatement action plans and formulation of revised ambient noise standards in Indian scenario.